Early Information About Bio-physical Quality of Seaweed Culture (Eucheuma cottonii) in Waworada Bay, Bima Regency - M. Sirajuddin (Jurnal Akuakultur Indonesia)
One of the potential areas for developing mariculture in West Nusa Tenggara Province is Waworada Bay of Bima Regency. The aim of this research was to find out the early information about bio-physical quality in Waworada Bay for sustainable development of seaweed culture. PCA (Principal Components Analysis) was used to explore the characteristic distribution of biophysics parameters, and then explore the relationship between seaweed production and carragenan content with biophysics parameters. GIS analysis was also applied to determine the suitable area for seaweed culture. PCA analysis shows that the main parameters of growth seaweed culture was light penetration, water current, water deepness, pest, salinity, nitrate and Pb. As additional parameters were temperature, COD, DO, Phosphate, and pH. Biophysics parameters were found to have very important relationship with seaweed growth, production and carragenan content. Based on GIS analysis, 11,128 ha of 11,135 ha was very ideal for seaweed culture, and the remaining was unsuitable for seaweed culture.